Perspectives on Fracture Liaison Service in Austria: clinical and economic considerations - Kocijan, Roland; Haschka, Judith; Kraus, Daniel Arian; Pfender, Aaron; Frank, Stefan; Zwerina, Jochen; Behanova, Martina (Frontiers in Endocrinology, 2024)
Osteoporosis is a widespread disease and affects over 500,000 people in Austria. Fragility fractures are associated with it and represent not only an individual problem for the patients, but also an enormous burden for the healthcare system. While trauma surgery care is well provided in Vienna, there is an enormous treatment gap in secondary prevention after osteoporotic fracture. Systematic approaches such as the Fracture Liaison Service (FLS) aim to identify patients with osteoporosis after fracture, to clarify diagnostically, to initiate specific therapy, and to check therapy adherence. The aim of this article is to describe the practical implementation and operational flow of an already established FLS in Vienna. This includes the identification of potential FLS inpatients, the diagnostic workup, and recommendations for an IT solution for baseline assessment and follow-up of FLS patients. We summarize the concept, benefits, and limitations of FLS and provide prospective as well as clinical and economic considerations for a city-wide FLS, managed from a central location. Future concepts of FLS should include artificial intelligence for vertebral fracture detection and simple IT tools for the implementation of FLS in the outpatient sector.